Comportamiento epidemiológico de la Rinotraqueitis infecciosa bovina. - Donoso Vega, Lisbeth Mariela (2022)
The present research has as its goal, to evaluate the epidemiological behavior of Infectious Bovine Rhinotracheitis in the province of Cotopaxi, using the ELISA-i technique. A statistical study was done for the behavior’s analysis, by collecting blood samples from 396 bovines, divided into 12 for each town, the obtained information from the owners was done through an interview, to carry out an analysis of variables which one is related to the disease. There is presence of IBR in the province of Cotopaxi since, of the 396 sampled bovines, 161 positive cases were obtained distributed as follows: the highest prevalence was found in Pangua canton with 72.2% followed by La Maná with 58.3 %, Sigchos represents 56.2%, while Salcedo canton has 38.3%, Latacunga with 31.6%, and the lowest prevalence is found in Pujilí and Saquisilí cantons with 30.5%. The risk factors that got a relationship with the prevalence of the disease were age with 0.02133 and race with 0.0003793 due to its p value is less than 0.05. The epidemiological map displays the canton with the highest percentage of prevalence and the number of positive cases per town.